Correlation between acidic ninhydrin and HPLC methods to evaluate fraudulent addition of whey in milk - Fukuda, S. P.; Roig, S. M.; Prata, L. F. (E D P Sciences, 2004)
The acidic ninhydrin spectrophotometric method (ANSM) for quantitative determination of free and bound sialic acid of milk glycoprotein has been proved to be fast and efficient for routine detection of fraudulent addition of rennet whey to fluid milk. In this research the ANSM was compared with the high performance liquid chromatography (HPLC) method, internationally recommended for caseinomacropeptide (CMP) determination, which besides its high accuracy is more sophisticated and requires trained personnel. For several sample conditions (raw milk and milk with variable added amounts of rennet cheese whey), the methods showed an excellent linear correlation, with r = 0.981 when milk was deproteinized with a 120 g.L-1 final concentration of trichloroacetic acid (TCA) concentration. The best correlations could be seen with final concentrations of 100 g.L-1 and 80 g.L-1 TCA; respectively, r = 0.992 and 0.993.
Keywords: Milk; adulteration; whey; addition; acidic ninhydrin; HPLC